Ett stycke rörd natur: Agrilogistik och ängshävd hos Fredrik Nyberg och Birgitta Lillpers - Roberg, Sofia (Passage - Tidsskrift for litteratur og kritik, 2026)
Disturbed Nature: Agrilogistics and the Poetics of the Meadow in Fredrik Nyberg and Birgitta Lillpers This article examines poetic representations of the meadow in Fredrik Nyberg’s Att bli ved and Slingorna och undergången and Birgitta Lillpers’ Anteckningar om hö through Timothy Morton’s concepts of agrilogistics and dark ecology. The meadow – shaped by human practice yet marked by its exuberant biodiversity – becomes a site where nature and culture intertwine. Nyberg explores it as a metapoetic form, while Lillpers links haymaking to care, decay, and renewal.